2016
DOI: 10.1103/physrevd.94.105008
|View full text |Cite
|
Sign up to set email alerts
|

Radiative processes of two entangled atoms outside a Schwarzschild black hole

Abstract: We consider radiative processes of a quantum system composed by two identical two-level atoms in a black-hole background. We assume that these identical two-level atoms are placed at fixed radial distances outside a Schwarzschild black hole and interacting with a quantum electromagnetic field prepared in one of the usual vacuum states, namely the Boulware, Unruh or the Hartle-Hawking vacuum states. We study the structure of the rate of variation of the atomic energy. The intention is to identify in a quantitat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 116 publications
0
29
1
Order By: Relevance
“…Dalibard, Dupont-Roc and Cohen Tannoudji(DDC) proposed that a symmetric ordering should be exploited, so that the contributions of field fluctuations and radiation reaction can be distinctively separated [72,73]. This formalism has been widely used to study the spontaneous transition rates and energy shifts of a single atom interacting with quantum fields in various environments [2, 6-12, 15-19, 22-24], and very recently, it was generalized to study the resonance interaction between two atoms prepared in an entangled state in the Minkowski spacetime [4,71,[79][80][81][82] and in the Schwarzschild spacetime [25,82]. Here we introduce the DDC formalism with which we will investigate the resonance interaction energy of two atoms in the Minkowski and cosmic string spacetimes.…”
Section: The Ddc Formalismmentioning
confidence: 99%
“…Dalibard, Dupont-Roc and Cohen Tannoudji(DDC) proposed that a symmetric ordering should be exploited, so that the contributions of field fluctuations and radiation reaction can be distinctively separated [72,73]. This formalism has been widely used to study the spontaneous transition rates and energy shifts of a single atom interacting with quantum fields in various environments [2, 6-12, 15-19, 22-24], and very recently, it was generalized to study the resonance interaction between two atoms prepared in an entangled state in the Minkowski spacetime [4,71,[79][80][81][82] and in the Schwarzschild spacetime [25,82]. Here we introduce the DDC formalism with which we will investigate the resonance interaction energy of two atoms in the Minkowski and cosmic string spacetimes.…”
Section: The Ddc Formalismmentioning
confidence: 99%
“…Moreover, it has also been employed to investigate the radiative processes of entangled atoms in Minkowski spacetime [19] and also in the presence of an event horizon [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning this last subject, studies reported recently confirm the relevance of the field of relativistic quantum information as a vivid research program [58][59][60]. Since, as already quoted above, the DDC formalism was sucessfully employed in order to study quantum entanglement [37][38][39], a natural extension of such papers is to include the investigation of entanglement generation between atoms in Kerr spacetime resorting to the same method. On the other hand, one could envisage the same situation within a more standard formalism such as the traditional master equation approach.…”
Section: Discussionmentioning
confidence: 96%